Dynamics of the distribution of marriages of churchgoers of the Grado-Tyumen Assumption Church in Tyumen in 1863–1867 - I. S. Ivanchenko (Вестник Майкопского государственного технологического университета, 2023)
The article is based on the materials of the church registers of the Grado-Tyumen Assumption Church in the city of Tyumen, the Tyumen district, the Tobolsk province, and analyzes the features of marital behavior and the dynamics of the distribution of marriages in the city of Tyumen in 1863–1867 in order to find out how and with what intensity the changes occurred in the traditional values of premarital and marital behavior in this territory. This fact substantiates the relevance of the research, since without a comprehensive analysis of the dynamics of the distribution of marriages and identification of the characteristics of marital behavior, it is impossible to fully imagine the social and economic evolution of the city of Tyumen as the largest and most important commercial and industrial center of Russia beyond the Urals. Various aspects of the marital behavior of the inhabitants of the city of Tyumen in the Tobolsk province in the second half of the 19th century have been considered on the basis of modern methodological principles of gender studies; situations with secondary and subsequent marriages, interclass marriages, and marriages with immigrants have been studied. The position of widows of soldiers and their attractiveness as brides in the territory of the Tyumen district has also studied, and the reasons for marriages with a large age difference in favor of the bride identified. A conclusion has been made about the features of marital behavior and the parameters of the distribution of weddings during the year, the age of marriage and the social origin of the spouses.